A kind of ferulic acid-electrochemical synergistic auxiliary blast furnace slag pre-carbonization preparation low-carbon high-performance cement mortar and method

CN122916484APending Publication Date: 2026-10-16DALIAN MARITIME UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611192196.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]然而,现有技术仍有不足之处:其一,高炉渣活性激发不充分,高掺量替代水泥时早期强度往往不够,限制了这类固废的实际利用比例;其二,预碳化时间一旦过长,C-S-H凝胶容易过度脱钙,后期强度反而增长缓慢甚至回落,预碳化时长、固碳量与强度增益三者难以兼顾;其三,现有强碱性激发剂或部分有机改性剂在激发矿渣活性的同时,容易破坏预碳化所需的适宜pH环境,且易产生二次污染、成本偏高、能耗大,与绿色建材的方向并不契合

Benefits of technology

(1)采用可从麦麸、玉米芯等农林废弃物中提取的天然绿色材料阿魏酸激发高炉渣活性,替代传统强碱性化学激发剂,避免二次污染。支持高炉渣在混凝土及水泥基材料中的大掺量应用,减少固废堆存占地与环境压力,提升工业固废资源化利用水平。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916484A_ABST
    Figure CN122916484A_ABST
Patent Text Reader

Abstract

The application discloses a kind of ferulic acid-electrochemical synergistic auxiliary blast furnace slag pre-carbonization methods for preparing low-carbon high-performance cement mortar.The method comprises: ferulic acid is added to mix water solution, blast furnace slag powder is prepared into slag slurry;While continuously passing in carbon dioxide and stirring, apply direct current field, and carry out synergistic pre-carbonization;Reach preset time, stop, replace cement with pre-carbonized blast furnace slag according to 40% of total mass of cementitious material, and mix uniformly with remaining cement, standard sand and water, pour test mold and standard curing, obtain cement mortar.The application utilizes ferulic acid and direct current field to synergistically stimulate slag activity, promote calcium carbonate fine crystallization, significantly improve early and late strength of mortar, preferably pre-carbonization 20 min, ferulic acid 0.2 g, 7 d and 28 d compressive and flexural strength are optimal;Realize industrial solid waste large-volume utilization, CO2 mineralization sequestration and high performance synchronous improvement, green and low carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of low-carbon building materials manufacturing technology, and in particular to a method for preparing low-carbon high-performance cement mortar by ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonization. Background Technology

[0002] Cement production involves significant CO2 emissions, making it a major source of carbon emissions in the building materials industry. Cement and concrete production account for approximately 7-8% of global annual carbon emissions. my country produces more than half of the world's cement, and the cement industry's carbon emissions account for over 10% of the country's total carbon emissions. Furthermore, it is included in the national carbon emissions trading market, making a low-carbon transformation imperative. Meanwhile, blast furnace slag, a major industrial solid waste generated from steel smelting, not only occupies land but also poses environmental risks when stored. Whether it can be fully and extensively utilized in cement-based materials directly impacts the actual effectiveness of solid waste reduction and carbon emission reduction in the building materials industry. To address this, existing technologies mainly follow these routes: First, replacing some cement clinker with solid wastes such as blast furnace slag and fly ash to reduce cement usage; second, using CO2 pre-carbonization curing to react CO2 with calcium-containing components in the slurry to generate calcium carbonate, fixing gaseous CO2 in mineral form and simultaneously improving early strength; third, using chemical methods such as alkali activators to activate slag activity; and fourth, some studies have attempted to introduce an external electric field to assist ion migration, but this is mostly used for permeability assessment or accelerating hydration and has not yet been widely applied to pre-carbonization carbon fixation systems.

[0003] However, existing technologies still have shortcomings: First, the activation of blast furnace slag activity is insufficient, and the early strength is often insufficient when high-dosage slag is used to replace cement, which limits the actual utilization rate of this type of solid waste; Second, if the pre-carbonization time is too long, CSH gel is prone to excessive decalcification, and the strength growth in the later stage is slow or even declines, making it difficult to balance the pre-carbonization time, carbon fixation amount and strength gain; Third, existing strong alkaline activators or some organic modifiers, while activating slag activity, are prone to destroying the suitable pH environment required for pre-carbonization, and are prone to secondary pollution, high cost and high energy consumption, which are not in line with the direction of green building materials.

[0004] Therefore, there is an urgent need for a cement mortar preparation method that can take into account both early and late strength, further improve the resource utilization level of blast furnace slag, and be more green and low-carbon. Summary of the Invention

[0005] This invention provides a method for preparing low-carbon, high-performance cement mortar by ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonation, in order to overcome the above-mentioned problems.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows: This invention provides a method for preparing low-carbon, high-performance cement mortar through ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonation, comprising the following steps: (1) Add ferulic acid to an appropriate amount of mixing water and stir until completely dissolved to prepare a ferulic acid solution; (2) Add blast furnace slag powder to the ferulic acid solution obtained in step (1) and stir continuously to prepare a uniform slag slurry; (3) Carbon dioxide is continuously introduced into the slag slurry to carry out a pre-carbonization reaction. During the reaction, the slurry is continuously stirred and a DC electric field is applied to make the electrochemical action and the carbon dioxide mineralization reaction proceed simultaneously. (4) After the preset carbonization reaction time is reached, stop the introduction of carbon dioxide and DC electric field, and terminate the reaction to obtain pre-carbonized blast furnace slag slurry; (5) The pre-carbonized blast furnace slag slurry is mixed with cement to prepare a mixed cementitious material; (6) Add standard sand and mixing water to the mixed cementitious material, stir thoroughly to prepare a mortar mixture; (7) The mortar mixture is poured into a mold and cured under standard curing conditions to obtain the cement mortar.

[0007] Further, the purity of ferulic acid in step (1) is 97%, and the amount added is 0.1~0.3 g; the amount of blast furnace slag powder added in step (2) is 210 g; the amount of standard sand added in step (6) is 1312.5 g; and the total amount of mixing water added in steps (1) and (6) is 262.5 g.

[0008] Further, by mass, the mass ratio of cement to pre-carbonized blast furnace slag slurry in the mixed cementitious material described in step (5) is 2:3.

[0009] Furthermore, the method of applying the DC electric field in step (3) is as follows: using a carbon rod as the anode and a steel bar as the cathode, and connecting an adjustable DC regulated power supply.

[0010] Furthermore, in step (3), the time for continuously introducing carbon dioxide is the same as the time for applying the DC electric field, and the preset carbonization reaction time is 5~25 min.

[0011] Furthermore, the blast furnace slag powder mentioned in step (2) is S105 grade finely ground blast furnace slag powder.

[0012] Furthermore, the cement mentioned in step (6) is P·Ⅰ42.5 silicate cement.

[0013] Furthermore, the casting test molds mentioned in step (7) are a 50 mm × 50 mm × 50 mm cube test mold and a 40 mm × 40 mm × 160 mm prism test mold, and are compacted using a vibration table.

[0014] Furthermore, the standard curing conditions described in step (7) are a temperature of (20±2)℃ and a relative humidity of ≥95%.

[0015] In another aspect, the present invention provides a low-carbon, high-performance cement mortar prepared by the above-described preparation method.

[0016] The beneficial effects of this invention are: (1) Ferulic acid, a natural green material that can be extracted from agricultural and forestry wastes such as wheat bran and corn cobs, is used to activate the activity of blast furnace slag, replacing traditional strong alkaline chemical activators and avoiding secondary pollution. This supports the large-scale application of blast furnace slag in concrete and cement-based materials, reducing the land occupation and environmental pressure of solid waste storage, and improving the level of industrial solid waste resource utilization.

[0017] (2) Applying an external electric field to accelerate the Ca in the pore solution 2+ CO3 2- The directional migration and mass transfer of plasma improves the rate and depth of CO2 dissolution, conversion and carbonization reaction, significantly increases the amount of CO2 fixed per unit pre-carbonization time, and mineralizes and seals gaseous CO2 in the cement matrix, thus helping the concrete industry to fix carbon and reduce emissions.

[0018] (3) Ferulic acid continuously promotes the dissolution of the calcareous phase in blast furnace slag and replenishes the formation of CSH gel. In synergy with the fine crystallization effect of electric field-assisted carbonization products, it achieves simultaneous improvement of solid waste, carbon fixation and mechanical properties. It takes into account both early and late strength development, avoids the problem of strength decline in the later stage of traditional pre-carbonization, and lays the foundation for the application of this technology to large-volume structural materials such as concrete. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 This is an overall schematic diagram of the preparation method described in this invention; Figure 2 The compressive strength of the cement mortar prepared by this invention at various curing ages under different pre-carbonation assisted methods; Figure 3The flexural strength of the cement mortar prepared by this invention at various curing ages under different pre-carbonation assisted methods; Figure 4 The compressive strength of the cement mortar prepared by this invention under different ferulic acid addition amounts and assisted precarbonation methods is given. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] Example 1.1 The experimental materials used in the following examples are as follows: P·Ⅰ 42.5 silicate cement (OPC 42.5), S105 grade finely ground blast furnace slag powder (G) and standard sand (S) were all purchased externally; ferulic acid is a phenolic acid compound that is naturally found in the cell walls of plants such as wheat bran and corn cobs. The ferulic acid used in this invention can be obtained by commercially available reagents or by plant extraction; the mixing water is laboratory tap water (W).

[0023] A type of ferulic acid A method for preparing low-carbon, high-performance cement mortar by electrochemical synergistic-assisted precarbonization of blast furnace slag, such as... Figure 1 The specific preparation method is as follows: (1) Preparation of ferulic acid solution: By mass (1 part equals 1 g), prepare 2.5 parts of P·Ⅰ4 silicate cement, 315 parts of S105 grade finely ground blast furnace slag powder, 1312.5 parts of standard sand, 262.5 parts of total mixing water, 0.2 parts of ferulic acid with a purity of 97%, a carbon dioxide cylinder, an adjustable DC regulated power supply, a carbon rod, and reinforcing steel bars. Add 0.2 parts of ferulic acid to part of the mixing water and stir on a magnetic stirrer until completely dissolved to obtain a ferulic acid solution.

[0024] (2) Preparation of slag slurry: 210 parts of S105 grade finely ground blast furnace slag powder were added to the ferulic acid solution obtained in step (1) and continuously stirred with magnetic force to prepare a uniform slag slurry.

[0025] (3) Synergistic precarbonation: Carbon dioxide is continuously introduced into the slag slurry to carry out precarbonation reaction. During the reaction, the slurry is continuously magnetically stirred. At the same time, a DC electric field (voltage 30 V, current changes continuously as the reaction proceeds) is applied to the slurry by connecting an adjustable DC regulated power supply with a carbon rod as the anode and a steel bar as the cathode, so that the electrochemical action and the carbon dioxide mineralization reaction proceed synchronously. The preset carbonation reaction time is 20 min.

[0026] (4) Termination of reaction: After 20 min, stop the introduction of carbon dioxide and DC electric field, and terminate the reaction to obtain pre-carbonized blast furnace slag slurry.

[0027] (5) Mixed cementitious material: The obtained precarbonized blast furnace slag slurry was mixed with 315 parts of P·Ⅰ42.5 silicate cement to prepare mixed cementitious material (the precarbonized blast furnace slag slurry accounted for 40% of the total mass of cementitious material).

[0028] (6) Preparation of mortar mixture: Add 1312.5 parts of standard sand to the mixed cementitious material and add the remaining mixing water. Mix thoroughly with an automatic cement mortar mixer to prepare the mortar mixture.

[0029] (7) Molding and curing: The mortar mixture was poured into 50 mm×50 mm×50 mm cube molds and 40 mm×40 mm×160 mm prism molds respectively. After being vibrated on a vibrating table, the molds were placed in a standard curing room with a temperature of (20±2)℃ and a relative humidity of ≥95% for curing. The resulting cement mortar specimens were marked as GFE20.

[0030] Example 1.2 Unlike Example 1, the carbonation reaction time in step (3) is preset to 5 min, and the remaining steps are the same as in Example 1. The resulting cement mortar specimen is marked as GFE5.

[0031] Example 1.3 Unlike Example 1.1, the carbonation reaction time in step (3) is preset to 10 min, and the remaining steps are the same as in Example 1.1. The resulting cement mortar specimen is marked as GFE10.

[0032] Example 1.4 Unlike Example 1.1, the carbonation reaction time in step (3) is preset to 15 min, and the remaining steps are the same as in Example 1.1. The resulting cement mortar specimen is marked as GFE15.

[0033] Example 1.5 Unlike Example 1.1, the carbonation reaction time in step (3) is preset to 25 min, and the remaining steps are the same as in Example 1.1. The resulting cement mortar specimen is marked as GFE25.

[0034] Example 2.1 Unlike Example 1.1, 0.1 parts of ferulic acid were added in step (1), and the carbonization reaction time in step (3) was preset to 10 min. The remaining steps were the same as in Example 1.1.

[0035] Example 2.2 Unlike Example 1.1, 0.3 parts of ferulic acid were added in step (1), and the carbonization reaction time was preset to 10 min in step (3). The remaining steps were the same as in Example 1.1.

[0036] Comparative Example 1 (Cement Control Group) Unlike Example 1.1, this comparative example omits the steps of preparing blast furnace slag slurry in (1) to (4) of Example 1.1. Instead, it only mixes cement with standard sand and mixing water to prepare a mortar mixture. The experimental parameters and proportions are the same as in Example 1.1. After being molded and cured under the same conditions as in Example 1.1, cement specimens are obtained and marked as C0.

[0037] Comparative Example 2 Unlike Example 1.1, this comparative example omits steps (1), (3), and (4) of Example 1.1, i.e., it does not add ferulic acid solution, does not introduce CO2, and does not apply a DC electric field. The remaining experimental conditions are the same as in Example 1.1, and the resulting cement mortar specimens are marked as G0.

[0038] Comparative Example 3.1 (Pre-carbonized group alone) Unlike Example 1.1, this comparative example did not include ferulic acid solution and did not apply a DC electric field. All other experimental conditions were the same as in Example 1.1. The specific preparation steps are as follows: S105 grade finely ground blast furnace slag powder (G) was weighed and added to an appropriate amount of mixing water. The mixture was then continuously stirred on a magnetic stirrer to prepare a uniform slag slurry. Carbon dioxide was continuously introduced during the stirring process to initiate a pre-carbonization reaction. The slurry was continuously stirred throughout the reaction to promote sufficient contact between the carbon dioxide and the slag particles, thereby improving the pre-carbonization reaction efficiency. The pre-carbonization time was set to 20 minutes. Once the preset reaction time was reached, the carbon dioxide supply was stopped and the reaction was terminated, yielding a slag slurry with the corresponding degree of pre-carbonization. The obtained pre-carbonized blast furnace slag was used to replace 40% of the total mass of P·I42.5 silicate cement with the remaining 60% of the cement as a mixed cementitious material. Standard sand and mixing water were added, and the mixture was stirred evenly using an automatic cement mortar mixer to prepare standard cement mortar specimens. The resulting cement mortar specimens were labeled G20.

[0039] Comparative Example 3.2 Unlike Comparative Example 3.1, the pre-carbonation time was set to 5 min, and the remaining steps were the same as in Comparative Example 1. The resulting cement mortar specimens were marked as G5.

[0040] Comparative Example 3.3 Unlike Comparative Example 3.1, the pre-carbonation time was set to 10 min, and the remaining steps were the same as in Comparative Example 1. The resulting cement mortar specimens were marked as G10.

[0041] Comparative Example 3.4 Unlike Comparative Example 3.1, the pre-carbonation time was set to 15 min, and the remaining steps were the same as in Comparative Example 1. The resulting cement mortar specimens were marked as G15.

[0042] Comparative Example 3.5 Unlike Comparative Example 3.1, the pre-carbonation time was set to 25 min, and the remaining steps were the same as in Comparative Example 1. The resulting cement mortar specimens were marked as G25.

[0043] Comparative Example 4.1 (Ferulic Acid-Assisted Precarbonization Group) Unlike Example 1.1, no DC electric field was applied in this comparative example, but the other experimental conditions were the same as in Example 1.1, and the resulting cement mortar specimens were labeled GF20.

[0044] Comparative Example 4.2 Unlike Example 1.1, no DC electric field was applied in this comparative example, and the pre-carbonation time was set to 5 min. The other experimental conditions were the same as in Example 1.1, and the resulting cement mortar specimens were labeled GF5.

[0045] Comparative Example 4.3 Unlike Example 1.1, no DC electric field was applied in this comparative example, and the pre-carbonation time was set to 10 min. The other experimental conditions were the same as in Example 1.1, and the resulting cement mortar specimens were labeled GF10.

[0046] Comparative Example 4.4 Unlike Example 1.1, no DC electric field was applied in this comparative example, and the pre-carbonation time was set to 15 min. The other experimental conditions were the same as in Example 1.1, and the resulting cement mortar specimens were marked as GF15.

[0047] Comparative Example 4.5 Unlike Example 1.1, no DC electric field was applied in this comparative example, and the pre-carbonation time was set to 25 min. The other experimental conditions were the same as in Example 1, and the resulting cement mortar specimens were labeled GF25.

[0048] Comparative Example 5.1 Unlike Example 2.1, this comparative example only introduces carbon dioxide for pre-carbonization treatment, without applying a DC electric field to assist pre-carbonization; the remaining steps are the same as in Example 2.1.

[0049] Comparative Example 5.2 Unlike Example 2.2, this comparative example only introduces carbon dioxide for pre-carbonization treatment, without applying a DC electric field to assist pre-carbonization; the remaining steps are the same as in Example 2.2.

[0050] Performance Test and Experiment Results like Figure 4 As shown, the results indicate that within the ferulic acid addition range of 0.1 g to 0.3 g, the compressive strength of the sample significantly increases as the ferulic acid addition increases from 0.1 g to 0.2 g; however, when the ferulic acid addition further increases to 0.3 g, the compressive strength of the sample decreases. This suggests that insufficient ferulic acid cannot fully exert its regulatory effect on the pre-carbonization products of slag, while excessive ferulic acid will adsorb onto the surface of slag particles, inhibiting the ion dissolution and carbonization reaction process, and weakening the mechanical properties of the sample. Based on the above experimental results, under the same process conditions of this invention, the optimal addition amount of ferulic acid is determined to be 0.2 g, with a suitable addition range of 0.1 g to 0.3 g, thus providing optimal process parameters for subsequent overall pre-carbonization experiments. Based on this optimal addition amount (0.2 g), this invention further adjusts the proportions of other components and experimental conditions, and, in conjunction with the accompanying drawings, further explains its beneficial effects.

[0051] The proportions of each component and precarbonation conditions in the cement mortar specimens obtained in Examples 1.1 to 1.5 and Comparative Examples 1.1 to 4.5 are shown in Table 1: Table 1. Mix proportions and pre-carbonization conditions for each experimental group

[0052] This invention prepares cement mortar specimens with different pre-carbonation methods according to the above method, and tests and evaluates their mechanical properties. Based on... Figure 2 Compared with the compressive strength test results shown in Table 2, and Figure 3 As shown in Table 3, the flexural strength test results indicate that the ferulic acid-electric field synergistic blast furnace slag precarbonation method adopted in this invention can significantly improve the mechanical properties of cement mortar.

[0053] Table 2 Comparison of 7-day and 28-day compressive strength of pre-carbonized, ferulic acid, ferulic acid and electric field-assisted pre-carbonized cement mortars

[0054] Note: Growth rate = (compressive strength of test group) (C0 group compressive strength) / (C0 group compressive strength) × 100% Table 3. Comparison of 7-day and 28-day flexural strength of pre-carbonized, ferulic acid, ferulic acid, and electric field-assisted pre-carbonized cement mortars.

[0055] Note: Growth rate = (flexural strength of the test group) (Flexural strength of group C0) / (Flexural strength of group C0) × 100% like Figure 2 , Figure 3 As shown in Tables 2 and 3, in order to verify the influence of the various technical features of the present invention on the mechanical properties of cement mortar, the 40% blast furnace slag replacement group (G0), the blast furnace slag pre-carbonization group (G series), the ferulic acid assisted pre-carbonization group (GF series), and the ferulic acid-electric field synergistic pre-carbonization group (GFE series) were compared and analyzed with the blank control group (C0).

[0056] Without pre-carbonation treatment, the 7-day and 28-day compressive strengths of group G0 increased by 20.88% and 7.80% respectively compared to group C0, while the 7-day and 28-day flexural strengths increased by 3.27% and 2.67% respectively, indicating that the addition of blast furnace slag has a certain improvement on early strength, but the improvement is limited. After pre-carbonation treatment, the 28-day compressive strength of the G series specimens at pre-carbonation times of 5, 10, 15, 20, and 25 min increased by 13.74%, 18.1%, 23.34%, 26.97%, and 22.58% respectively compared to group C0, while the 28-day flexural strength increased by 8.81%, 10.30%, 23.77%, 23.85%, and 11.41% respectively. The improvement in 7-day strength generally followed the same trend as that of 28-day strength. It can be seen that pre-carbonation treatment can significantly improve the mechanical properties of cement mortar, and the strength growth rate first increases and then decreases with the pre-carbonation time, reaching a relatively optimal level at around 20 min.

[0057] After introducing ferulic acid on the basis of precarbonation, the 28-day compressive strength of the GF series increased by 28.53%, 35.03%, 45%, 51.81%, and 41.54% respectively compared with the C0 group, and the 28-day flexural strength increased by 10.63%, 23.59%, 24.93%, 26.69%, and 19.26% respectively. The 7-day strength growth rate also increased, indicating that ferulic acid modification can further enhance the mechanical properties of cement mortar on the basis of precarbonation. After further introducing electric field assistance, the 28-day compressive strength of the GFE series increased by 33.74%, 39.38%, 52.17%, 61.43%, and 53.99% respectively compared with the C0 group, and the 28-day flexural strength increased by 11.80%, 24.03%, 31.33%, 31.63%, and 19.57% respectively. The 7-day compressive strength growth rates were 37.71%, 59.43%, 67.71%, 69.98%, and 49.53% respectively, and the 7-day flexural strength growth rates were 26.42%, 44.19%, 50.57%, 59.97%, and 54.46% respectively, all of which were the highest levels among all groups. Among them, the 7-day and 28-day compressive strengths of the GFE20 group were 54.677 MPa and 76.88 MPa respectively, and the 7-day and 28-day flexural strengths were 10.622 MPa and 12.665 MPa respectively, which were the optimal values ​​under various pre-carbonization time conditions.

[0058] Based on the above comparisons, it can be seen that the effects of blast furnace slag replacement, pre-carbonation treatment, ferulic acid modification, and electric field assistance on improving the mechanical properties of cement mortar increase in that order. Among them, the pre-carbonation treatment (GFE series) under the synergistic effect of ferulic acid and electric field has the best effect, and the two have a synergistic strengthening effect. Moreover, when the pre-carbonation time is 20 min, the compressive strength and flexural strength of GFE series specimens at 7d and 28d both reach the optimal level, which is the preferred pre-carbonation time of this invention.

[0059] Mechanism of ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonization: Blast furnace slag is rich in calcium components, mainly existing in the form of amorphous calcium aluminum silicate glass, which has potential hydraulic activity. During the pre-carbonation process, CO2 dissolves in the slurry to form carbonic acid, which reacts with the calcium mineral phase in the slurry, releasing calcium ions. These calcium ions may originate from Ca(OH)2 generated by the hydration of active CaO in the slag, or they may directly originate from the dissolution and release of the slag glass structure under acidic conditions. The dissolved Ca²⁺ + It then reacts with CO3² in the solution. - The two molecules combine to form calcium carbonate precipitate, and the reaction can be represented as follows: CaO + H₂O → Ca(OH)₂ CO2 + H2O → H2CO3 Ca(OH)₂ + CO₂ → CaCO₃↓ + H₂O At the same time, the hydrated calcium silicate gel (CSH) formed on the surface of blast furnace slag will also undergo a certain degree of decalcification reaction, generating calcium carbonate and releasing amorphous silica. The reaction can be represented as follows: 3CaO·2SiO2·3H2O+3CO2→3CaCO3+2SiO2·nH2O+(3-n)H2O.

[0060] The calcium carbonate generated in the above reaction can effectively fill the pores inside the slurry and improve the density of the matrix. This is the main reason why the strength of the specimens treated only with pre-carbonation is improved compared to the untreated blank control group. However, although the hardness and solid volume of calcium carbonate are higher than those of CSH gel, and it makes a positive contribution to the strength improvement in the early stage of the carbonation reaction, if the degree of carbonation continues to deepen, the excessive consumption of CSH gel will weaken its continuous contribution to the strength development. The experimental results of this invention also show that the strength growth rate of the specimens treated only with pre-carbonation first increases and then tends to level off or even decline with the extension of the pre-carbonation time. This is consistent with the above-mentioned CSH gel consumption mechanism, indicating that it is difficult to achieve a continuous improvement in strength by simply extending the pre-carbonation time. It is urgent to optimize and control the reaction process through other auxiliary means.

[0061] Ferulic acid, as a weak acid, contains both carboxyl and phenolic hydroxyl functional groups in its molecular structure. When added to blast furnace slag cement slurry, it can undergo an acid-base neutralization reaction with the dissolved calcium components in the slurry, thus improving the strongly alkaline environment around the slurry to a certain extent and promoting the dissolution and release of active silicate and aluminate components in the blast furnace slag. Simultaneously, the carboxyl groups in ferulic acid can react with the dissolved Ca²⁺... + Ion association or coordination occurs, further accelerating the dissolution process of the active component. Since ferulic acid is a weak acid, its H... + The release of the active ingredient is relatively mild and will not cause a sharp drop in the pH of the system. In addition, the continuous dissolution of the active ingredient can gradually increase the alkalinity of the solution. Therefore, while promoting the dissolution of the active substance, it can still maintain the strong alkaline reaction environment required for the formation of CSH gel. This allows the introduction of ferulic acid to achieve the early activation of the activity of blast furnace slag without inhibiting the normal hydration reaction, and to continuously replenish the CSH gel content in the system, thereby compensating to some extent for the adverse effect of CSH consumption on strength development during the pre-carbonization process.

[0062] Under the condition of simultaneously applying an electric field and introducing CO2, on the one hand, the system temperature under the influence of the electric field will show a certain upward trend with the duration of energization. This thermal effect can increase the solubility of calcium-containing components such as calcium hydroxide, thus increasing the Ca²⁺ concentration in the solution. + The concentration further increased; on the other hand, the directional migration of charged ions driven by the electric field accelerated the Ca²⁺ concentration. +CO3²⁻ produced by dissolving CO2 - HCO3 - The high mass transfer efficiency of plasma shortens the path and time required for ions to diffuse to reactive sites, thereby increasing the formation rate of calcium carbonate. Simultaneously, the carboxyl and phenolic hydroxyl functional groups in ferulic acid can adsorb onto newly formed calcium carbonate nuclei and crystal growth interfaces via hydrogen bonding or ion association, inhibiting the directional growth of grains and promoting the development of carbonation products towards finer and more homogeneous crystals, resulting in smaller and more uniformly distributed calcium carbonate particles. These fine, uniform calcium carbonate particles can serve as nanoscale fillers, more fully filling the pores of the slurry and the surface of blast furnace slag particles, further enhancing the density of the matrix.

[0063] In summary, a synergistic strengthening effect may exist between ferulic acid modification and electric field assistance: on the one hand, ferulic acid compensates for the adverse effect of CSH consumption on strength development during simple carbonization by promoting the dissolution of active components and continuously replenishing CSH gel; on the other hand, the electric field accelerates ion mass transfer efficiency and increases the formation rate of calcium carbonate, while the ferulic acid functional groups further inhibit grain coarsening and promote the fine crystallization of carbonization products. This synergistic mechanism is consistent with the experimental results of this invention: compared with specimens that have only undergone pre-carbonization treatment (G series) and specimens that have only undergone pre-carbonization treatment with ferulic acid doping (GF series), the ferulic acid-electric field synergistic pre-carbonized specimens (GFE series) not only show a more significant strength gain in the early stage of the pre-carbonization reaction, but this gain effect can also be maintained until the later age, without the phenomenon of slowing strength growth in the later stage of simple pre-carbonization treatment. This indicates that the synergistic effect of ferulic acid and electric field has a positive promoting effect on the balanced development of CSH gel and calcium carbonate reaction products during the carbonization reaction. Furthermore, this invention also observed that when the pre-carbonization time was extended to a longer stage, the strength growth rate of each series of specimens decreased to varying degrees. It is speculated that this may be because the carbonation products gradually accumulate and thicken on the surface of the blast furnace slag particles and the pore surface of the slurry, forming a dense calcium carbonate layer that, to some extent, hinders the reaction of CO2 and Ca. 2+ The further diffusion and transport of reactants into the unreacted areas inside the slurry limits the continued and sufficient progress of the deep carbonization reaction. This provides mechanistic support for the present invention to optimize the pre-carbonization time within a moderate range.

[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing low-carbon, high-performance cement mortar by ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonization, characterized in that, Includes the following steps: (1) Add ferulic acid to an appropriate amount of mixing water and stir until completely dissolved to prepare a ferulic acid solution; (2) Add blast furnace slag powder to the ferulic acid solution obtained in step (1) and stir continuously to prepare a uniform slag slurry; (3) Carbon dioxide is continuously introduced into the slag slurry to carry out a pre-carbonization reaction. During the reaction, the slurry is continuously stirred and a DC electric field is applied to make the electrochemical action and the carbon dioxide mineralization reaction proceed simultaneously. (4) After the preset carbonization reaction time is reached, stop the introduction of carbon dioxide and DC electric field, and terminate the reaction to obtain pre-carbonized blast furnace slag slurry; (5) The pre-carbonized blast furnace slag slurry is mixed with cement to prepare a mixed cementitious material; (6) Add standard sand and mixing water to the mixed cementitious material, stir thoroughly to prepare a mortar mixture; (7) The mortar mixture is poured into a mold and cured under standard curing conditions to obtain the cement mortar.

2. The method for preparing low-carbon, high-performance cement mortar by ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonization according to claim 1, characterized in that, The purity of ferulic acid in step (1) is 97%, and the amount added is 0.1~0.3 g; the amount of blast furnace slag powder added in step (2) is 210 g; the amount of standard sand added in step (6) is 1312.5 g; the total amount of mixing water added in steps (1) and (6) is 262.5 g.

3. The method for preparing low-carbon, high-performance cement mortar by ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonization according to claim 1, characterized in that, By mass, the mass ratio of cement to pre-carbonized blast furnace slag slurry in the mixed cementitious material described in step (5) is 2:

3.

4. The method for preparing low-carbon, high-performance cement mortar by ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonization according to claim 1, characterized in that, The method of applying the DC electric field in step (3) is as follows: a carbon rod is used as the anode and a steel bar is used as the cathode, and an adjustable DC regulated power supply is connected.

5. The method for preparing low-carbon, high-performance cement mortar by ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonization according to claim 1, characterized in that, In step (3), the continuous carbon dioxide flow time is the same as the DC electric field application time, and the preset carbonization reaction time is 5~25 min.

6. The method for preparing low-carbon, high-performance cement mortar by ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonization according to claim 1, characterized in that, The blast furnace slag powder mentioned in step (2) is S105 grade finely ground blast furnace slag powder.

7. The method for preparing low-carbon, high-performance cement mortar by ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonization according to claim 1, characterized in that, The cement mentioned in step (6) is P·Ⅰ42.5 silicate cement.

8. The method for preparing low-carbon, high-performance cement mortar by ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonization according to claim 1, characterized in that, The casting test molds mentioned in step (7) are a 50 mm × 50 mm × 50 mm cube test mold and a 40 mm × 40 mm × 160 mm prism test mold, and are compacted by a vibration table.

9. The method for preparing low-carbon, high-performance cement mortar by ferulic acid-electrochemical synergistic assisted blast furnace slag precarbonization according to claim 1, characterized in that, The standard curing conditions described in step (7) are a temperature of (20±2)℃ and a relative humidity of ≥95%.

10. A low-carbon, high-performance cement mortar, characterized in that, It is prepared by any one of the preparation methods described in claims 1-9.